Fabrication of polysaccharide-based nanoparticles as drug delivery nanocarriers - Pang, S.C; Chin, S.F.; Nadirah, A.; Tay, S.H.; Yazid, S.N.A.M (Electrochemical Society Inc., 2015)
Polysaccharide-based nanoparticles have been developed as drug delivery nanocarriers for encapsulating and releasing optimum doses of drug at targeted sites over a predictable period of time. We have reported herein the successful loading of curcumin onto both native starch and starch-maleate nanoparticles prepared via in-situ nanoprecipitation in aqueous medium and water-in-oil emulsion, respectively. The physico-chemical characteristics of curcumin-loaded polysaccharide-based nanoparticles such as sizes, porosity, and hydrophilicity or hydrophobicity were subsequently optimized by tailoring synthesis parameters which include solvents, surfactants, cross-linkers, and polysaccharide precursors. Under optimum conditions, native starch nanoparticles with a mean diameter of 87 nm exhibited a maximum curcumin loading efficiency of 78%. Curcumin was observed to release from native starch nanoparticles at physiological pH in sustained and predictable manners over a period of 10 days. On the other hand, the diameter of curcumin-loaded starch-maleate nanoparticles varied between 30 nm and 110 nm and a mean diameter of 50 nm. The loading of curcumin onto starch-maleate nanoparticles occurred rapidly initially but declined gradually until the curcumin loading capacity of 15 mg/g was achieved within 12 hours. Curcumin-loaded starch-maleate nanoparticles exhibited a water solubility of 6.0 x 10-2 mg/mL, which was about 300 times higher than that of free curcumin. Increased water solubility coupled with desirable loading capacity and release kinetic profile of curcumin in polysaccharide-based nanoparticles should, in turn, lead to enhanced bioavailability of curcumin. The potential utility of native starch and starch-maleate nanoparticles as cost-effective polysaccharide-based drug delivery nanocarriers is therefore envisaged.